“It's All Sort of Cool and Interesting…but What Do I Do With It?” A Qualitative Study of Stroke Survivors' Perceptions of Surface Electromyography - Feldner, Heather A.; Papazian, Christina; Peters, Keshia; Steele, Katherine M. (Frontiers in Neurology, 2020)
Background: Stroke is one of the most common neurologic injuries worldwide. Over decades, evidence-based neurorehabilitation research and advancements in wireless, wearable sensor design have supported the deployment of technologies to facilitate recovery after stroke. Surface electromyography (sEMG) is one such technology, however, clinical application remains limited. To understand this translational practice gap and improve clinical uptake, it is essential to include stakeholder voices in an analysis of neurorehabilitation practice, the acceptability of current sEMG technologies, and facilitators and barriers to sEMG use in the clinic and the community. The purpose of this study was to foreground the perspectives of stroke survivors to gain a better understanding of their experiences in neurorehabilitation, the technologies they have used during their recovery, and their opinions of lab-designed and commercially-available sEMG systems. Methods: A qualitative, phenomenological study was completed. In-depth, semi-structured interviews were conducted with eight stroke survivors (age range 49-78 years, 6 months to 12 years post-stroke) and two caregivers from a large metropolitan region. A demonstration of four sEMG systems was provided to gather perceptions of sensor design, features and function, and user interface. Interviews were audio-recorded, transcribed verbatim, and coded for analysis using constant comparison until data saturation was reached. Results: Three themes emerged from the data: 1) ‘Surface EMG has potential….but…’ highlights the recognition of sEMG as a valuable tool but reveals a lack of understanding and need for clear meaning from the data; 2) ‘Tracking incremental progress over days or years is important’ highlights the persistence of hope and potential benefit of sEMG in detecting small changes that may inform neurorehabilitation practice and policy; and 3) ‘Neurorehabilitation technology is cumbersome’ highlights the tension between optimizing therapy time and trying new technologies, managing cost, logistics and set-up, and desired technology features. Conclusion: Further translation of sEMG technology for neurorehabilitation holds promise for stroke survivors, but sEMG system design and user interface needs refinement. The process of using sEMG technology and products must be simple and provide meaningful insight to recovery. Including stroke survivors directly in translational efforts is essential to improve uptake in both clinical and community environments.